Learning From Elite Athletes’ Experience of Depression - Lebrun, Florence; MacNamara, Àine; Rodgers, Sheelagh; Collins, Dave (Frontiers in Psychology, 2018)
Abstract Sport has become increasingly aware of the challenges associated with Mental Disorders and, to a greater extent, Mental Health Issues or MHIs. This study sought to explore in depth the subjective experiences of elite athletes who suffered from a specific clinical MHI, namely depression. In addition, we explored their perceptions of the prevalence and stigma surrounding MHIs in elite sport environments. Data were collected from four elite athletes (1 female and 3 males; 2 team and 2 individual sports) using semi-structured interviews and analysed using Interpretative Phenomenological Analysis (IPA). Participants described both sport and non-sport related triggers in regard to their depression (e.g. institutional mistreatment and bullying, injuries, previous MHI, and miscarriage), as well as a range of behaviour, performance (e.g. decline), and personality changes compared to their normal functioning. Although the participants stressed the widespread prevalence of MHIs in elite sport, they also acknowledged the stigma associated with MHIs in high-level sport environments and its detrimental role for athletes. This study has important practical and diagnostic implications, and highlights the need for further research to assess the extent and scope of clinical MHIs in sport as well as to inform the care for this unique population.